Pemanfaatan Antibodi Monoklonal Dalam I-Elisa Untuk Deteksi Penyebab Penyakit Busuk Pucuk Kelapa (Phythophthora Palmivora) - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Pascasarjana Universitas Gadjah Mada, 1999)
Mice monoclonal antibodies (MCAs) against Phytophthora palmivora, Butl. (the pathogen of coconut bud rot) have been produced and tested. The selected hybridoma tAbPM.3 secreted monoclonal antibodies of IgM subclass and the titer in vitro of 10--111.. employed to develop Indirect-Enzyme Linked Ininumosorbent Assay. This assay was able to differentiate coconut isolate of P. palmivora not only from cocoa and pepper isolate of the same species. but also front other fungus isolated front coconut bud rot diseased coconut (Fusarium sp.. Colletotrichum sp., and Thielaviopsis sp.). This (ISS(I1' was able to differentiate P. palmivora isolate from diseased coconut with those isolated from cocoa and pepper, and adze,- fungus isolated front diseased coconut, thereby providing specific diagnostic tool for coconut bud rot which is needed for supporting the application of the concept of integrated pest mange/nem on coconut.